The impact of future socio-economic and climate changes on agricultural land use and the wider environment in East Anglia and North West England using a metamodel system - Audsley, Eric; Pearn, Kerry R.; Harrison, P. A.; Berry, P. M. (Springer Science Business Media, 2008)
This paper describes a procedure to use a model interactively to investigate future land use by studying a wide range of scenarios defining climate, technological and socio-economic changes. A full model run of several hours has been replaced by a metamodel version which takes a few seconds, and provides the user with an immediate visual output and with the ability to examine easily which factors have the greatest effect. The Regional Impact Simulator combines a model of agricultural land use choices linked with models of urban growth, flooding risk, water quality and consequences for wildlife to estimate plausible futures of agricultural land on a timescale of 20–50 years. The model examines the East Anglian and North West regions of the United Kingdom at a grid resolution of 5 × 5 km, and for each scenario estimates the most likely cropping and its profitability at each location, and classifies land use as arable, intensive or extensive grassland or abandoned. From a modelling viewpoint the metamodel approach enables iteration. It is thus possible to determine how product prices change so that production meets demand. The results of the study show that in East Anglia cropping remains quite stable over a wide range of scenarios, though grassland is eliminated in scenarios with the 2050s High climate scenario – almost certainly due to the low yield in the drier conditions. In the North West there is a very much greater range of outcomes, though all scenarios suggest a reduction in grassland with the greatest in the 2050s High climate scenario combined with the “Regional Stewardship” (environmental) socio-economic scenario. The effects of the predicted changes in land use on plant species showed suitability for species to vary greatly, particularly between the socio-economic scenarios, due to detrimental effects from increases in nitrogen fertilisation. A complete simulation with the Regional Impact Simulator takes around 15 seconds (computer-dependent), which users who responded felt was adequate or better than adequate. The main areas for future improvement, such as the speed of the system, user interaction and the accuracy and detail of the modelling, are co